Influence of Warehouse Management Practices on Service Delivery in Zimbabwean Local Authorities - Munyaradzi Chibaro; Augustine Torayi Mataba; Cynthia Mupfiga (Research Synergy Press, 2024)
The study assessed the influence of warehouse management practices on service delivery in Zimbabwean urban local authorities. The study was underpinned by three theories, namely the theory of inventory and production, the application control theory and adaptive structuration theory of warehouse management practice problems. The study was informed by post positivism philosophy. The study employed cross-sectional descriptive survey and data was gathered from respondents using structured questionnaires. Cronbach's alpha was used to assess data reliability. Five hypotheses that passed the validity and normalcy tests were examined using structural equation modelling. For data analysis, SPSS version 21 and AMOS version 21 were utilized. The statistical analysis and results demonstrated a correlation between the independent variables (enterprise resource planning, order processing, inventory lead time and materials handling on service delivery). The analysis showed that development and implementation of service delivery in the local authorities has been marred with challenges of declined warehouse management practices. The findings showed that urban local authorities’ service delivery has been struggling to perform as anticipated due to problems of fluctuating inventories, inaccurate forecast, poor responsiveness to customer’s needs and lack of proper technological systems resulting to poor services delivered to tax payers. The study concluded that warehouse management practices have a strong influence on service delivery for urban local authorities. The study recommended study the adoption of some strategic stance towards warehouse management practices. It was also reckoned that urban local authorities need to deliberately adopt electronic warehouse management practices to enhance service delivery.